Enhancing Worker Safety Behaviors Through Proactive Interventions in the Lifting and Transport Equipment Industry - Zuhroh, Ervira Fatimatuz; Wiediartini; Riantini, Rona; Ariany, Zulfaidah (MEIN : Journal of Mechanical, Electrical & Industrial Technology, 2024)
Unsafe worker behavior remains a prevalent issue leading to workplace accidents, particularly within companies specializing in services for head truck operations, maintenance, and lifting equipment. This study aims to enhance worker safety behaviors through proactive interventions utilizing behavioral observation and intervention (BO&I). Additionally, trend analysis is employed to predict the impact of interventions on worker safety behaviors. Mechanical workers involved in lifting and transport equipment operations are surveyed as respondents. The findings reveal a notable increase in the percentage of safe behaviors post-intervention compared to pre-intervention levels. Moreover, disparities in worker safety behaviors between pre- and post-intervention stages are identified, particularly in work stages associated with a high frequency of accidents. Trend analysis forecasts that the maximum percentage of safe worker behavior will be observed at the 91st intervention. Furthermore, binary logistic regression analysis indicates that variables such as age, tenure, utilization of personal protective equipment (PPE), and education significantly influence worker behaviors.